2020
DOI: 10.1007/s11897-019-00450-1
|View full text |Cite
|
Sign up to set email alerts
|

Reappraisal of Inflammatory Biomarkers in Heart Failure

Abstract: Purpose of Review Inflammation has been shown to be an important factor in the development and progression of heart failure (HF), regardless of the etiology. There have been many studies demonstrated roles of inflammatory biomarkers in diagnosis, prognosis of chronic and acute HF patients, and also markers of cardiotoxicity from chemotherapy. These cytokines are highsensitivity C-reactive protein (hsCRP), myeloperoxidase (MPO), soluble growth stimulation expressed gene 2 (sST2), interleukin-6 (IL-6), tumor nec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
22
0
1

Year Published

2020
2020
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 29 publications
(23 citation statements)
references
References 167 publications
(154 reference statements)
0
22
0
1
Order By: Relevance
“…We found that, in males, LV mass increased in proportion to serum IL-6 levels. IL-6 is a pro-inflammatory cytokine implicated in the pathogenesis of hypertrophy and heart failure ( 50 ). It binds to IL-6 receptors on cardiomyocytes and promotes cardiac hypertrophy in adult male rats ( 51 ).…”
Section: Discussionmentioning
confidence: 99%
“…We found that, in males, LV mass increased in proportion to serum IL-6 levels. IL-6 is a pro-inflammatory cytokine implicated in the pathogenesis of hypertrophy and heart failure ( 50 ). It binds to IL-6 receptors on cardiomyocytes and promotes cardiac hypertrophy in adult male rats ( 51 ).…”
Section: Discussionmentioning
confidence: 99%
“…B‐type natriuretic peptide (BNP) is one of the gold standard biomarkers in determining the diagnosis and prognosis of HF 17 . Tumour necrosis factor‐α (TNF‐α) and interleukin‐1β (IL‐1β) have been demonstrated as inflammatory biomarkers in chronic and acute HF patients 18 . LDH locates in the cytoplasm of cardiomyocytes in normal state.…”
Section: Methodsmentioning
confidence: 99%
“…17 Tumour necrosis factor-α (TNF-α) and interleukin-1β (IL-1β) have been demonstrated as inflammatory biomarkers in chronic and acute HF patients. 18 After cDNA was ligated with adaptors, PCR amplification was performed using Phusion High-Fidelity DNA polymerase, Universal PCR primers and Index (X) Primer and build the library of each sample.…”
Section: Detection Of Biomarkersmentioning
confidence: 99%
“…Galectin‐3 is systemically released, from fibroblast and macrophage, on active inflammation sites and is implicated during the early stages of certain systemic diseases such as endothelial dysfunction, CHD, and heart failure 9 . Moreover, it has been demonstrated that Galectin‐3, similarly to asymmetric dimethylarginine, 10 reduces the release of nitric oxide (NO) from macrophages and downregulates some pro‐inflammatory cytokines such as tumor necrosis factor‐alpha (TNF‐α) and IL‐1β 11 . Galectin‐3 has also been shown to regulates the apoptosis of T‐helper cells through the stimulation of IL‐10 and −21 12 .…”
Section: Introductionmentioning
confidence: 99%